Pengaruh Model Pembelajaran Talking Stick terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas VIII SMP Negeri 1 Siborongborong Tahun Pembelajaran 2023/2024 - Lestari Sinaga; Rusmauli Simbolon; Johari Manik; Sudirman Lase; Rida Gultom (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
The aim of this research is to determine the positive and significant influence of the talking stick learning model on the active learning of Christian Religious Education for class VIII students at SMP Negeri 1 Siborongborong for the 2023/2024 academic year. The method used in this research uses a quantitative approach with inferential descriptive data analysis. The population is all students in class VIII of SMP Negeri 1 Siborongborong for the 2023/2024 academic year, 256 Protestant Christians and a sample of 48 people, namely 20%, was determined using random sampling. Data was collected using a positive closed questionnaire with 40 items. The results of data analysis show that there is a positive and significant influence of the talking stick learning model on the learning activity of Christian Religious Education for class VIII students at SMP Negeri 1 Siborongborong for the 2023/2024 academic year: 1) Test the analysis requirements: a) test a positive relationship with a value of rxy = 0.550 > rtable(α=0.05,n=48) = 0.284, thus it is known that there is a positive relationship between variable dk=n-2=46)= 2.021, thus there is a significant relationship between variable b) Regression coefficient of determination test (r2) = 30.3%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(α=0.05, dk numerator k=24, dk denominator=n-2=48-2=46) namely 19.95 > 1.51. Thus Ha is accepted and H0 is rejected.